Evaluasi Keandalan Perencanaan Pembangkit Wilayah Jawa-Bali dengan Mempertimbangkan Ketidakpastian Peramalan Beban - Avrin Nur Widiastuti; Sarjiya; Kukuh Arung Pinanditho; Eko Tri Prastyo (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2017)
Power system reliability is one of important aspects of power system operation. Lack of capacity in the generation system will affect reliability level of the power system. System evaluation needs to be done to know whether the system is still reliable to supply the load that is projected to increase 8.2% per year. Java-Bali system evaluation planning period 2015-2024 is conducted in this paper. Load forecast uncertainty (LFU) is one of the parameters that needs to be considered when conducting system planning. It is because load tends to be uncertain. This research uses two scenarios: without and with load forecast uncertainty. Reliability indexes LOLE and LOLP are used to evaluate the Java-Bali system. All calculations are based on a program using MATLAB. The result shows that reliability indexes LOLE and LOLP are higher with considering LFU. It means reliability decreases, rather than planning without considering LFU. Moreover, Java-Bali system reliability indexes meet the PLN’s standard value with the best value acquired in 2019.